Jordan : Second Review Under the Extended Arrangement Under the Extended Fund Facility, Requests for a Waiver of Nonobservance of Performance Criterion, an Extension of the Arrangement, and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for Jordan. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Jordan's Second Review under the Extended Arrangement under the Extended Fund Facility, Requests for a Waiver of Nonobservance of Performance Criterion, an extension of the arrangement, and rephasing of access. Discussions highlight that the Jordanian authorities have preserved macroeconomic stability, maintain a prudent monetary policy, and ensured a sound financial system. Jordan faces a challenging environment-including low economic growth, high unemployment, and elevated public debt-underscoring the importance of swiftly implementing policies and reforms to bring public debt on a downward path, boost investment and productivity, and enhance inclusive growth. The enactment of long needed growth-enhancing reforms is encouraging, including the secured transactions law, the bankruptcy law, and the business-inspections law. The international community has strongly supported the new government's commitment to maintain the reform momentum, strengthen growth, and reduce public debt. The London Initiative in February 2019 has helped unlock essential budget grants and concessional financing to support the authorities' reform program.